Web based interactive family photo album (N-IFPA) - Norul Nazifah, Yusuff (2015)
Web based interactive family photo album (N-IFPA) is built to show the web based development for the family photo album that will contain a few of interactive features such as tagging photo and family live chat. The family tree will be manually generic by updating the relationship of the family members. By the existence of this web based application, it can help the relationship between the family members to be closer because the family members can know each other more precisely by just follow up this application. The relatives can enter the information about their family members and the relationship between them and this web based will be manually update the family tree to make the families know the new status of the relationship with each of the family members. The purpose useful of this application is could help the new born family members to know their relatives closely by looking at their photo and relationship among them. In manual method, each of family members sometimes felt the difficulties to get to know each other among their family members. With this system architecture, it can help the family members to get the information in a proper way. This Web based application use the Waterfall method as a development phase that can operate the phases step by step.